2020
DOI: 10.5194/os-2020-27
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An explicit estimate of the atmospheric nutrient impact on global oceanic productivity

Abstract: Abstract. State-of-the-art global nutrient deposition fields are here coupled to the biogeochemistry model PISCES to investigate the effect on ocean biogeochemistry in the context of atmospheric forcings for preindustrial, present, and future periods. Present-day atmospheric deposition fluxes of inorganic N, Fe, and P over the global ocean are accounted equal to ~40 Tg-N yr−1, ~0.28 Tg-Fe yr−1 and ~0.10 Tg-P yr−1. The resulting globally integrated primary production of roughly 47 Pg-C yr−1 is well within the r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
(110 reference statements)
1
0
0
Order By: Relevance
“…This is reasonably consistent with field observations, which showed that higher Fe solubilities for finer aerosols influenced by BB and fossil fuel combustion sources but no such trend for mineral dustdominated aerosols (Siefert et al 1999;Buck et al 2010;Kumar et al 2010;Trapp et al 2010). Recent ocean biogeochemistry models included combustion sources (e.g., fuel combustion and biomass burning) of bioavailable Fe in addition to mineral dust (Hamilton et al 2020;Hajima et al 2020;Ito et al 2020;Myriokefalitakis et al 2020). However, the magnitude of their response to the atmospheric input of L Fe was substantially different.…”
Section: Aerosol Fe Source Apportionment In the Eastern Shsupporting
confidence: 86%
“…This is reasonably consistent with field observations, which showed that higher Fe solubilities for finer aerosols influenced by BB and fossil fuel combustion sources but no such trend for mineral dustdominated aerosols (Siefert et al 1999;Buck et al 2010;Kumar et al 2010;Trapp et al 2010). Recent ocean biogeochemistry models included combustion sources (e.g., fuel combustion and biomass burning) of bioavailable Fe in addition to mineral dust (Hamilton et al 2020;Hajima et al 2020;Ito et al 2020;Myriokefalitakis et al 2020). However, the magnitude of their response to the atmospheric input of L Fe was substantially different.…”
Section: Aerosol Fe Source Apportionment In the Eastern Shsupporting
confidence: 86%